A new species of spine-headed katydid Mesagraecia Ingrisch, 1998 (Conocephalinae: Agraeciini), with key to species - Tan, Ming Kai; Ingrisch, Sigfrid; Kamaruddin, Khairul Nizam (Zootaxa, 2015)
The taxonomy of poorly known Mesagraecia Ingrisch, 1998 is reviewed. A new species of Mesagraecia spine-headed katydid (Conocephalinae: Agraeciini) is described from Bukit Larut, Perak, Peninsular Malaysia: Mesagraecia larutensis sp. n. A key to species is also presented.